Psychometric Evaluation of a Turkish Version of the Diabetes Fear of Self-injecting and Self-testing Questionnaire (D-FISQ) - Selda Celik, RN, PhD; Rukiye Pinar, RN, PhD (Elsevier, 2016)
Purpose: To examine the psychometric properties of a Turkish version of the Diabetes Fear of Injecting and Self-testing Questionnaire (D-FISQ). Methods: Forward-backward translation of the D-FISQ from English into Turkish was conducted. Original English and translated forms were examined by a panel group. Validity was investigated using content, confirmatory factor analysis, and divergent validity. Reliability was assessed using Cronbach α values, item-total correlations, and intraclass correlations. The sample comprised 350 patients with diabetes. Data were analyzed using SPSS 15.0 for Windows and LISREL 8. Results: The content validity index for the panel members was .90, which indicated perfect content validity; items in D-FISQ were clear, concise, readable, and distinct. Confirmatory factor analysis confirmed the original construct of the D-FISQ. All items had factor loadings higher than the recommended level of .40. The D-FISQ scores were discriminated by the level of anxiety. Reliability results were also satisfactory. Cronbach α values were within ideal limits. Item-total correlation coefficient ranged from .72 to .86. In terms of test-retest reliability, intraclass correlation coefficient was found to be over .90. Conclusions: D-FISQ is a valid and reliable questionnaire in assessing needle-prick fear among Turkish patients with diabetes. We recommend performing the Turkish D-FISQ in determining and screening patients with diabetes who have fear related to self-insulin injection and finger-prick test. Thus, health care professionals should be aware of the potential consequences of injection fear such as insulin misuse and poor self-monitoring of blood glucose, which may have unfavorable effects on optimal diabetes management.